Performance of quality protein maize (Zea mays) genotypes under different moisture-stress environments - PARIHAR, A K; GODAWAT, S L; SHUKLA, K B; PARIHAR, C M (The Indian Journal of Agricultural Sciences, 2012)
Eightysix genotypes of quality protein maize (Zea mays L.) including 12 parents, their 66 crosses and 7 checks were evaluated for morpho-physiological traits in four environments created by withdrawing irrigation at different crop growth stages in winter (rabi) season of 2009–10. Hybrids exhibited higher grain yield/plant and low chlorophyll stability index in stress condition, were found good for stress environments. The traits under investigation were governed by additive and non-additive gene action and thus could be improved through selection, followed by hybridization. Among the good general combining inbreds with high per se performance for grain yield was P7 and P12. Among the hybrids, P9 × P12 and P4 × P12 were found best for all the environments but P10 × P12, P1 × P7, P1 × P4 were best only in well irrigated environments. The above hybrids also exhibited higher estimates of specific combining ability effects, economic heterosis and per-se performance in all the environments for grain yield/plant and chlorophyll stability index (CSI).